Roadblocks to the Socialist Modernization Path and Transition Evidence from East Germany and Poland - Günther, Jutta; Jajeśniak-Quast, Dagmara; Ludwig, Udo; Wagener, Hans-Jürgen (Studies in Economic Transition, 2024)
This open access book examines how different economic systems impacted the development of East Germany and Poland. Through comparing these countries while they were centrally planned socialist economies with the periods when they transitioned to capitalism, the inability of socialist economies to modernize effectively and produce sustained economic growth is highlighted. Particular attention is given the role of technological progress in economic growth, peculiar institutions, the creation and transfer of knowledge, and post-socialist transformations. The book presents a detailed analysis of the barriers to modernization and growth implied by Soviet-type state socialism and the differences and similarities between the transition of East Germany and Poland to capitalist market economies. It will be relevant to students and researchers interested in comparative systems and the political economy.